Proceedings of OCEANS 2005 MTS/IEEE
DOI: 10.1109/oceans.2005.1640100
|View full text |Cite
|
Sign up to set email alerts
|

ROV Serviceable Science Node for Cabled Ocean Observatories

Abstract: year life cabled ocean observatories are being planned with deep-sea and/or shallow water science nodes connected to the shore by commercially off the shelf (COTS) submarine telecommunication equipment, providing ample electrical power and high bandwidth data communications interfaces for science experiments and monitoring projects. The COTS equipment housed within the science nodes are not yet designed or qualified to traditional submarine telecom standards and are known to be less reliable than the associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Vehicle ROV -Location camera and halogen through a watertight gland. These cables, power is supplied to the diode and the power to the video camera and a video signal is transmitted from the camera to the interior of the vehicle, which then is converted to a standard RS-485 and sent on kablolin (communication cable, Figure 5 mark 7) for the TV monitor supported by the operator [23]. The vehicle has four ballast tanks, positioned in the corners of the vehicle.…”
Section: Fig 6 Vehicle Rov -Dimensionsmentioning
confidence: 99%
“…Vehicle ROV -Location camera and halogen through a watertight gland. These cables, power is supplied to the diode and the power to the video camera and a video signal is transmitted from the camera to the interior of the vehicle, which then is converted to a standard RS-485 and sent on kablolin (communication cable, Figure 5 mark 7) for the TV monitor supported by the operator [23]. The vehicle has four ballast tanks, positioned in the corners of the vehicle.…”
Section: Fig 6 Vehicle Rov -Dimensionsmentioning
confidence: 99%
“…Therefore, cost effective maintenance solutions have had to be found that do not require the use of a Cable lay Vessels (C/V) once initial installation and commissioning has been completed. To address this need for cost effective servicing of the science node, a ROV serviceable science node has been developed that allows the power and communications equipment housed within the node to be easily recovered and replaced by the same ROV equipped Research Vessel (R/V) used for deploying and servicing the science instruments [3]. Figure 5 gives an illustrated view of ROV operation with the node.…”
Section: Ocean Engineeringmentioning
confidence: 99%
“…Scientific research efforts with ROVs in the areas of marine archaeology (Conte et al, 2008;Rines, 2007), high-resolution video and geo-referenced bathymetric survey (Simeoni et al, 2007;Pinkard et al, 2005) and marine sampling (Ishibashi et al, 2008) are detailed in the literature and proposed new roles for ROVs, and other unmanned robotic vehicles in the installation and service of new cabled ocean observatories is detailed in Proctor et al (2007); Shepherd et al (2007), and Shaheen and Waterworth (2005). For geo-referenced data collection in particular, ROVs must increasingly accommodate more sophisticated instrument payload.…”
Section: Introductionmentioning
confidence: 99%